Bodybuilding anatomy - Evans, Nick (Human Kinetics, 2007)
Sculpt your physique like you never thought possible! With full-color, detailed anatomical illustrations of exercises, combined with step-by-step instructions on how to perform them, Bodybuilding Anatomy is the ideal resource for gaining mass and defining your muscles. Focusing on the primary muscle groups of shoulders, chest, back, arms, legs, and abdominals and targeting muscle zones and hard-to-work areas, Bodybuilding Anatomy can make the difference between bulking up and sculpting an award-winning physique. You will also learn how to modify exercise technique to influence results and individualize training programs according to your specific needs. Combining the expertise of MuscleMag International columnist, bodybuilder, and orthopedic surgeon Dr. Nick Evans with the talent of acclaimed bodybuilding artist Bill Hamilton, Bodybuilding Anatomy is the ultimate training guide for bodybuilders and dedicated strength trainers.